PROBLEMS AND THEIR SOLUTIONS IN THE FIELD OF IMPLEMENTATION OF AGREEMENTS BETWEEN UZBEKISTAN AND THE REPUBLIC OF KOREA ON THE PRACTICAL APPLICATION OF THE PRINCIPLES OF HIGHER EDUCATION (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article examines the challenges and potential solutions related to the implementation of agreements between Uzbekistan and the Republic of Korea on the practical application of higher education principles. Drawing upon the strengths of both educational systems, this partnership aims to enhance Uzbekistan's higher education sector. The study identifies key problems such as cultural differences, curriculum adaptation, administrative hurdles, and language barriers. Solutions are proposed, including fostering cultural exchange, joint curriculum development, streamlined administrative processes, and increased language support.